Peran Field Indonesia dalam Mitigasi Perubahan Iklim Melalui Program Udara Bersih Indonesia - Hanim, Syawelly; Apriwan; Setyaka, Virtuous (Palito, 2024)
This research aims to analyze the role of Field Indonesia as a Non Governmental Organization (NGO) in Indonesia that focuses on environmental issues. Field Indonesia sees the problem of climate change that must be addressed. Climate change occurs due to global warming caused by land burning activities. The impact of climate change in Indonesia is very concerning so that an effective solution is needed to overcome this problem. This research uses a qualitative method with a descriptive approach using primary and secondary data. This research uses the concept of Role of NGO Theory by Lucas J Giese which is seen through four indicators, namely issue framing, agenda setting, information provision, and lobbying & campaigning. This research describes that Field Indonesia plays a role in responding to climate change events by adopting the global climate change mitigation agenda. The mitigation agenda is focused on prevention efforts related to climate change through the Indonesian Clean Air Program. This study found that in carrying out its role as an NGO for program implementation, Field Indonesia framed the issue by conducting an initial survey of the community then developing a framework and establishing cooperation with various parties from local to international levels. Field Indonesia provides information related to the UBI Program through the Indonesian Clean Air Cadre Training activities and utilizes various digital platforms such as social media and websites, then Field lobbies and campaigns through journalist visits and poster distribution activities and obtains support related to the implementation of the UBI Program from the village level to the central government.